Prioritization of Health Education Techniques in Markazi Province Health Center through Analytical Hierarchy Process and Goal Programming - Mohammad Hossien Mehrolhassani; Rahmatollah Jadidi; Saeed Amini (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: Health education tries to provide an opportunity for people to find necessary information and skills to make high quality decisions.  One of the important steps for educational planning is selection of interventions that have most returns. The aim of this study was to prioritize health education methods through Analytical Hierarchy Process (AHP) and Goal Programming (GP) techniques. Materials and methods: This was a quantitative-qualitative and applied study. The sample consisted of all 12 city health centers in Markazi Province, Iran. Through Focus Group Discussions (FGDs), the main criteria of health education techniques were identified and prioritized through AHP technique. Then, using WinQSB software and GP program, the best combination of health education methods was determined. Results: Cost, access, acceptability, feasibility and effectiveness were identified as the main criteria for selection of health education methods. Prioritized training methods include, in order, were: group education (44.4%), face-to-face education (23%), distribution of pamphlets and brochures (10%), health education films (9%), sending educational SMS (7%), seminars (4%), TV education (1%), educational exhibitions (1%), role playing (0.5%) and educational rallies(0.10%). Conclusion: Methods of group education, face-to-face education, distribution of pamphlets and brochures and showing health educational films have a significant returns than other methods in terms of cost saving, meeting educational needs, target group access to educational methods, popularity and feasibility. Paper Type: Research Article.